2006
DOI: 10.1037/cjep2006004
|View full text |Cite
|
Sign up to set email alerts
|

Is there "feedback" during visual imagery? Evidence from a specificity of practice paradigm.

Abstract: The specificity of practice hypothesis predicts the development of a sensorimotor representation specific to the afferent feedback available during skill acquisition (Proteau, 1992; Proteau, Marteniuk, Girouard, & Dugas, 1987). In the present investigation, we used the specificity of practice hypothesis to test whether skill acquisition through visual imagery would lead to the development of a sensory-specific movement representation similar to one resulting from actual practice. To accomplish this objective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…Further, while the use of imagined movements can be intuitively associated with motor planning processes, it has also been proposed that imagined movements involve the emulation of online control mechanisms (e.g., Grush, 2004). Indeed, studies employing imagined actions can reflect the acquisition of online control mechanisms (Krigolson, Van Gyn, Tremblay, & Heath, 2006). Thus, attributions of the Fitts' Law violation to planning processes have largely ignored the possibility that placeholder manipulations could have affected online control.…”
Section: Discussionmentioning
confidence: 98%
“…Further, while the use of imagined movements can be intuitively associated with motor planning processes, it has also been proposed that imagined movements involve the emulation of online control mechanisms (e.g., Grush, 2004). Indeed, studies employing imagined actions can reflect the acquisition of online control mechanisms (Krigolson, Van Gyn, Tremblay, & Heath, 2006). Thus, attributions of the Fitts' Law violation to planning processes have largely ignored the possibility that placeholder manipulations could have affected online control.…”
Section: Discussionmentioning
confidence: 98%
“…In manual aiming toward visual targets, it has been proposed that early in practice, participants are able to determine the source(s) of afferent information that are more likely to ensure optimal accuracy, this role being mainly devoted to visual feedback processing (Coull, Tremblay & Elliott, 2001;Ivens & Marteniuk, 1997;Mackrous & Proteau, 2007;Proteau & Carnahan, 2001;. The increased reliance upon visual feedback has also been supported by study of gross motor tasks as walking (Krigolson et al, 2006;Proteau et al, 1998), powerlifting and sequential positioning (Ivens & Marteniuk, 1997). However, others studies challenged the visual dominance in motor control and learning, the detrimental effect of vision withdrawal decreasing with practice (Robin et al, 2004(Robin et al, , 2005Tremblay et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Proteau and collaborators (1987Proteau and collaborators ( , 1992Proteau and collaborators ( , 2001 observed that during video-aiming, participants who practiced the task with both visual and proprioceptive information (i.e., VP condition) were less accurate in a transfer test, when they had to perform the same task in a proprioceptive only condition (P condition), than participants who practiced it in a proprioceptive (P) condition. Moreover, the withdrawing of visual information on movement execution in transfer resulted either in a large deterioration in motor performance early during learning (i.e., after 20 trials; or in a deterioration that increased with practice (Blandin, Toussaint & Shea, 2008;Ivens & Marteniuk, 1997;Krigolson, Van Gyn, Tremblay & Heath, 2006;Proteau et al, 1987Proteau et al, , 1992Proteau et al, , 1998. Vision can thus be considered as the dominant sensory information for motor learning and control This dominance of visual cues was challenged in other works (Tremblay, Welsh & Elliott, 2001;Robin et al, 2004Robin et al, , 2005.…”
mentioning
confidence: 99%
“…Support for this idea can be found in a study that had participants either physically or mentally practice a special walking task in a specificity-ofpractice paradigm (Krigolson, Van Gyn, Tremblay, & Heath, 2006). In this paradigm, transfer is thought to depend on the similarity of visual or kinesthetic feedback available during acquisition and transfer.…”
mentioning
confidence: 93%